Molecular physicochemical parameters predicting antioxidant activity of Brazilian natural products - Scotti, Luciana; Scotti, Marcus Tullius; Mesquita Pasqualoto, Kerly Fernanda; Bolzani, Vanderlan da Silva [UNESP]; Ferreira, Elizabeth Igne (John Benjamins Publishing Company, 2009)
Reactive oxygen species (ROS) are capable of oxidizing cellular proteins, nucleic acids and lipids, contributing to cellular aging, mutagenesis, carcinogenesis, coronary heart and neurodegenerative diseases. Free radicals-scavenging by phenolic compounds occurs by the transfer of one electron followed by the H-abstraction. In order to evaluate the antioxidant activity of a series of seventeen phenolic compounds extracted from Brazilian flora (Chimarrhis turbinata and Arrabidea samydoides), some physicochemical parameters (heat formation of the neutral, radical, and cationic compounds; orbitals' energies; ClogP;Delta H(OX); and Delta H(f)) were calculated. Considering the results from the calculated descriptors, the molecules 10a-f can be classified as having a higher antioxidant activity.
Parâmetros físico-químicos na predição da atividade antioxidante de produtos naturais brasileiros
Keywords: Molecular modeling; phenolic compounds; antioxidant activity